Draft genome sequence of Halomonas sp. KHS3, a polyaromatic hydrocarbon-chemotactic strain - Gasperotti, Ana Florencia (2015)
The draft genome sequence of Halomonas sp. KHS3, isolated from seawater from Mar del Plata harbor, is reported. This strain is able to grow using aromatic compounds as a carbon source and shows strong chemotactic response toward these substrates. Genes involved in motility, chemotaxis, and degradation of aromatic hydrocarbons were identified.